2018
DOI: 10.3390/atmos9100376
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Land Cover Change on the Interannual Variability of Rainfall and Surface Temperature over West Africa

Abstract: We used the Abdu Salam International Centre for Theoretical Physics (ICTP) Regional Climate Model version 4.5 (RegCM4.5), to investigate the potential impacts of land cover change of the Sahel–Sahara interface on the West African climate over an interannual timescale from 1990 to 2009. A simulation at 50 km grid spacing is performed with the standard version of the RegCM4.5 model (control run), followed by three vegetation change experiments at the Sahel-Sahara interface (15° N and 20° N): forest, tall grass, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 71 publications
0
15
0
2
Order By: Relevance
“…Land use and land cover changes are known to influence the climate system [3]. Afforestation option is predicted to increase the rainfall over West Africa [51] while deforestation will reduce it [52]. Some study have shown how the change in vegetation affect the rainfall in the region [8,51].…”
Section: Discussionmentioning
confidence: 99%
“…Land use and land cover changes are known to influence the climate system [3]. Afforestation option is predicted to increase the rainfall over West Africa [51] while deforestation will reduce it [52]. Some study have shown how the change in vegetation affect the rainfall in the region [8,51].…”
Section: Discussionmentioning
confidence: 99%
“…The method of [45] is used to calculate the rainfall and temperature normalized anomalies over the West African domain (20 • W-20 • E; 5 • N-17.5 • N). This latter method is presented in details in [23]. Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The model description and the experimental setup are extensively described in [23]. Briefly, we used the default version of the International Center for Theoretical Physics (ICTP-Italy-Trieste) regional climate model RegCM4.5 as described in [24].…”
Section: Model Description and Experimental Set Upmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the study of the variability of climatic parameters is one of the major concerns of the scientific community [3][4][5]. That is why it is noted that the findings of researches are useful tools to assist decision-makers in the context of climate change [6].…”
Section: Introductionmentioning
confidence: 99%